DEFB1 gene 5′ untranslated region (UTR) polymorphisms are marginally involved in inflammatory bowel disease in south Brazilians. (12th September 2013) - Wilson, T. J.; Jobim, M.; Segat, L.; Bianco, A. M.; Salim, P. H.; Portela, P.; Jobim, L. F.; Damin, D. C.; Schwartsmann, G.; Roesler, R.; Crovella, S.
Summary The possible association of three DEFB1 gene polymorphisms with susceptibility to develop ulcerative colitis (UC) and Crohn's disease (CD) was investigated in Brazilian patients and controls. Although a clear and strong association between functional 5′‐UTR DEFB1 SNPs and susceptibility/protection to IBDs cannot be drawn, our results suggest a possible involvement of DEFB1 gene in inflammatory bowel diseases, especially with the colonic localization of Crohn's disease.